Photodegradation of Eumelanin and Pheomelanin and Its Pathophysiological Implications1. (26th October 2017) - Ito, Shosuke; Wakamatsu, Kazumasa; Sarna, Tadeusz
Abstract: Eumelanin is photoprotective for pigmented tissues while pheomelanin is phototoxic. In this review, we summarize current understanding of how eumelanin and pheomelanin structures are modified by ultraviolet A (UVA) and also by visible light and how reactive oxygen species participate in those processes. Alkaline hydrogen peroxide oxidation was employed to characterize eumelanin and benzothiazole‐type pheomelanin, giving pyrrole‐2, 3, 5‐tricarboxylic acid (PTCA) and thiazole‐2, 4, 5‐tricarboxylic acid (TTCA), respectively. Reductive hydrolysis with hydroiodic acid gives 4‐amino‐3‐hydroxyphenylalanine (4‐AHP) from the benzothiazine moiety of pheomelanin. The results show that the photoaging of eumelanin gives rise to free PTCA (produced by peroxidation in situ ) and pyrrole‐2, 3, 4, 5‐tetracarboxylic acid (PTeCA, produced by cross‐linking). The TTCA/4‐AHP ratio increases with photoaging, indicating the conversion of benzothiazine to the benzothiazole moiety. Analysis of those markers and their ratios show that both eumelanin and pheomelanin in human retinal pigment epithelium melanosomes undergo extensive structural modifications due to their lifelong exposure to blue light. Using synthetic melanins, we also found that singlet oxygen, in addition to superoxide anions, is photogenerated and quenched upon UVA irradiation. The (patho)physiological significance of those findings is discussed in relation to the tanning process, to melanomagenesis in the skin and to age‐related macular degeneration in the eyes. Abstract : Photo‐induced "aging" of melanin and its possible consequences are reviewed. We summarize how melanin structures are modified by ultraviolet A and blue light and how reactive oxygen species participates in those processes. The process of "aging" of melanin can be evaluated by spectrophotometry and HPLC analysis of melanin markers produced by chemical degradation methods. During photo‐aging, melanin undergoes deterioration of its roles in photoprotection and cytoprotection and generate superoxide anion and singlet oxygen. The (patho)physiological significance of those findings is discussed in relation to the tanning process, to melanomagenesis in the skin and to age‐related macular degeneration in the eyes.